2018
DOI: 10.5194/acp-18-11949-2018
|View full text |Cite
|
Sign up to set email alerts
|

Variations in surface ozone and carbon monoxide in the Kathmandu Valley and surrounding broader regions during SusKat-ABC field campaign: role of local and regional sources

Abstract: Abstract. Air pollution resulting from rapid urbanization and associated human activities in the Kathmandu Valley of Nepal has been leading to serious public health concerns over the past 2 decades. These concerns led to a multinational field campaign SusKat-ABC (Sustainable atmosphere for the Kathmandu Valley – Atmospheric Brown Clouds) that measured different trace gases, aerosols and meteorological parameters in the Kathmandu Valley and surrounding regions during December 2012 to June 2013 to understand loc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 61 publications
0
26
1
Order By: Relevance
“…The ratio of levoglucosan to mannosan (Lev/Man) has been applied to distinguish the possible categories of biomass burnt. Previously, higher Lev/Man ratios were reported for emissions from combustion of hardwood (ranging from 12.9 to 35.4 with an average of 21.5 ± 8.3) and agricultural residues (range from 12.7 to 55.7 with an average of 32.6 ± 19.1; Sang et al, 2013;Bhattarai et al, 2019). For the softwood burning, the average ratio was 4.0 ± 1.0 (ranging from 2.5 to 5.8).…”
Section: Anhydrosugarsmentioning
confidence: 94%
See 2 more Smart Citations
“…The ratio of levoglucosan to mannosan (Lev/Man) has been applied to distinguish the possible categories of biomass burnt. Previously, higher Lev/Man ratios were reported for emissions from combustion of hardwood (ranging from 12.9 to 35.4 with an average of 21.5 ± 8.3) and agricultural residues (range from 12.7 to 55.7 with an average of 32.6 ± 19.1; Sang et al, 2013;Bhattarai et al, 2019). For the softwood burning, the average ratio was 4.0 ± 1.0 (ranging from 2.5 to 5.8).…”
Section: Anhydrosugarsmentioning
confidence: 94%
“…Anhydrosugars of levoglucosan (1,6-anhydro-β-Dglucopyranose) and its two isomers (mannosan and galactosan) have been used as ideal molecular tracers for BB emissions (Simoneit, 2002;Bhattarai et al, 2019). They are exclusively emitted from the combustion and pyrolysis of cellulose and hemicelluloses.…”
Section: Anhydrosugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…South Asia is considered to be a major air pollution hotspot (Monks et al, 2009) and it is expected to be one of the most polluted regions in the world for surface ozone (O 3 ) and other pollutants by 2030 (Dentener et al, 2006;IEA, 2016;OECD, 2016). Past studies have shown that the air pollution from this region affects not only the region itself, but is also transported to other parts of the world, including comparatively pristine regions such as the Himalayas and the Tibetan Plateau (Bonasoni et al, 2010;Ming et al, 2010;Lüthi et al, 2015), as well as to other distant locations such as northern Africa and the Mediterranean (Lawrence and Lelieveld, 2010).The pollutants are also uplifted to the tropopause by convective air masses and transported to the extratropical stratosphere during the monsoon season (Tissier and Legras, 2016;Lawrence and Lelieveld, 2010;Fueglistaler et al, 2009;Highwood and Hoskins, 1998). Air pollution is particularly alarming in many urban areas of South Asia, including in the city of Kathmandu and the broader Kathmandu Valley, Nepal (Chen et al, 2015;Putero et al, 2015;Kim et al, 2015;Sarkar et al, 2016;Shakya et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…andPhys., 11, 9, 4039-4072, doi:10.5194/acp-11-4039-2011, 2011. (Simoneit et al, 1999) Fossil fuel combustion/evaporation Hopanes (Schauer et al, 1999) Food cooking Sterols (Rogge et al, 1991) Cow dung burning Stigmastanol (Sheesley et al, 2003) Garbage/plastic burning 1,3,5-Triphenylbenzene (Simoneit et al, 2005) Vegetative detritus n-Alkanes with odd carbon preference (Rogge et al, 1993) Isoprene SOA Methyltetrols (Kleindienst et al, 2007) Bhardwaj et al (2018); b) monthly average for January 2013; c) dash denotes data not available; d) standard error, e) NMVOC were measured 1305 continuously by PTR-MS, f) CO and CH 4 were measured continuously Atmos. Chem.…”
mentioning
confidence: 99%